Evaluation of Ivermectin as a Potential Treatment for Mild to Moderate COVID-19: A Double-Blind Randomized Placebo Controlled Trial in Eastern India - Ravikirti; Ranjini Roy; Chandrima Pattadar; Rishav Raj; Neeraj Agarwal; Bijit Biswas; Pramod Kumar Manjhi; Deependra Kumar Rai; Shyama; Anjani Kumar; Asim Sarfaraz (Frontiers Media S.A., 2021)
Background: There has been a growing interest in ivermectin ever since it was reported to have an in-vitro activity against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This trial was conducted to test the efficacy of ivermectin in mild and moderate coronavirus disease 19 (COVID-19). Methods: A double blind, parallel, randomised, placebo-controlled trial conducted among adult COVID-19 patients with mild to moderate disease severity on admission in a COVID dedicated tertiary healthcare of eastern India. Enrolment was done between 1st August and 31st October 2020.  On day 1 and 2 post enrolment, patients in the intervention arm received ivermectin 12 mg while the patients in the non-interventional arm received placebo tablets. Results: About one-fourth (23.6%) of the patients in the intervention arm and one-third (31.6%) in the placebo arm were tested reverse transcriptase polymerase chain reaction (RTPCR) negative for SARS-CoV-2 on 6th day. Although this difference was found to be statistically insignificant [rate ratio (RR): 0.8; 95% confidence interval (CI): 0.4-1.4; p=0.348]. All patients in the ivermectin group were successfully discharged. In comparison the same for the placebo group was observed to be 93%. This difference was found to be statistically significant (RR: 1.1; 95% CI; 1.0-1.2; p=0.045). Conclusions: Inclusion of ivermectin in treatment regimen of mild to moderate COVID-19 patients could not be said with certainty based on our study results as it had shown only marginal benefit in successful discharge from the hospital with no other observed benefits.